2013
DOI: 10.1126/scitranslmed.3006479
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Cardiomyocyte-Specific Kinase TNNI3K Limits Oxidative Stress, Injury, and Adverse Remodeling in the Ischemic Heart

Abstract: Percutaneous coronary intervention is first-line therapy for acute coronary syndromes (ACS) but can promote cardiomyocyte death and cardiac dysfunction via reperfusion injury, a phenomenon driven in large part by oxidative stress. Therapies to limit this progression have proven elusive, with no major classes of new agents since the development of anti-platelets/anti-thrombotics. We report that cardiac troponin I–interacting kinase (TNNI3K), a cardiomyocyte-specific kinase, promotes ischemia/reperfusion injury,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
105
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(109 citation statements)
references
References 30 publications
4
105
0
Order By: Relevance
“…Importantly, transgenic TNNI3K overexpression also resulted in marked worsening of mortality, cardiac function, and left ventricular remodeling. 9 The current work presented by Vagnozzi et al 3 supports the hypothesis that TNNI3K has a deleterious effect on the mammalian cardiac response to injury and that the inhibition of this kinase has a protective role.…”
Section: Abraham and Marchuksupporting
confidence: 67%
See 3 more Smart Citations
“…Importantly, transgenic TNNI3K overexpression also resulted in marked worsening of mortality, cardiac function, and left ventricular remodeling. 9 The current work presented by Vagnozzi et al 3 supports the hypothesis that TNNI3K has a deleterious effect on the mammalian cardiac response to injury and that the inhibition of this kinase has a protective role.…”
Section: Abraham and Marchuksupporting
confidence: 67%
“…However, in the current article, the genetic deletion of TNNI3K did not result in a significant change in hypertrophy in the basal state or after ischemic injury. 3 Although recent work has suggested that TNNI3K has a limited role in the regulation of sarcomeric proteins, recent work by both our group and other laboratories has suggested that this is not the case. Phosphorylation of cardiac troponin I is known to affect myofilament sensitivity and cardiac inotropy.…”
Section: Abraham and Marchukmentioning
confidence: 51%
See 2 more Smart Citations
“…NADPH autofluorescence was acquired using a 2-photon laser at 720 nm excitation and emission at 380-550 nm. Images were acquired using a Zeiss 710 Microscope equipped with 10× objective and a Coherent Chameleon 2-photon laser (48).…”
Section: Methodsmentioning
confidence: 99%